PERAN REWARD DAN PUNISHMENT DALAM MENUMBUHKAN KESADARAN MORAL SANTRI PP. ANNUQAYAH LUBANGSA - Zahrotul Jannah; M. Mahrus Ali (Living Sufism: Journal of Sufism and Psychotherapy, 2024)
This research aims to reveal the role of reward and punishment in growing the morale of PP. Annuqayah Lubangsa students by adopting Skinner and Piaget's thinking. The research method used is qualitative field research that seeks to analyze a person's behavior in a certain situation or place in detail with the main data source obtained. The type used is descriptive-analytical from 30 informants and complementary library data. The findings resulting from this paper are the rewards applied in PP. Annuqayah Lubangsa area takes the form of giving trophies, gifts, certificates and congratulations to students who excel in academic and non-academic fields. Meanwhile, the punishment imposed is to memorize, pray together behind the Kiai for 41 days and read the Koran. These two approaches have succeeded in improving the behavior of students and they can be easily guided and given direction by PP. Annuqayah Lubangsa administrators and caregivers. Thus, these two types of reinforcement are effective in growing the moral awareness of PP. Annuqayah Lubangsa students.